Student Engagement Mahasiswa UM Bandung: Sebuah Studi Komparatif pada Mahasiswa Reguler dan Non Reguler - Fara Berliana; Nurlaela Hamidah; Ainin Rahmanawati (Lembaga Pengkajian Pengembangan Pendidikan dan Kewirausahaan, 2024)
Student engagement is one of the indicators of academic success in higher education, including behavioral, emotional, and cognitive engagement in both regular and non-regular students. Regular class students generally have wider access to direct interaction with lecturers and peers, which can increase their academic engagement, while non-regular class students, such as employee classes or distance classes, face their own challenges in maintaining their engagement due to limited time and access to learning resources. This study aims to explore the differences in student engagement between regular and non-regular students at Universitas Muhammadiyah Bandung. The research method used was a quantitative method with a comparative approach. This study involved 426 subjects, with 279 regular students and 147 non-regular students at UM Bandung. The sampling technique used was disproportionate stratified random sampling. The results of the Mann-Whitney test showed that there was no significant difference in the level of student engagement between the two groups, with a significance value of 0.148 (p>0.05). This indicates that both regular and non-regular students have relatively the same level of learning engagement.